Invasi Bangsa Mongolia di Baghdad Sebagai Awal Kehancuran Literatur Islam - Arfah Ibrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The reign of the Abbasid dynasty reached its golden age during the reign of caliph Harun al-Rashid and caliph al-Ma'mun. At that time, literacy centers had developed, and the city of Baghdad was called a world professor because it had places of learning that gave birth to experts in several fields of knowledge, and became a center for translation facilities that translated many Arabic and non-Arabic books. However, in 1258 this dynasty entered a phase of destruction followed by the disappearance of scientific civilization as the Mongolian dynasty, which was then led by Hulagu Khan, came. The entire civilization of the Abbasid dynasty in Baghdad was destroyed and school buildings, mosques, universities and other buildings were torn down, all books were burned and thrown into the Tigris river, so that the river water turned black and many experts in the field of science were killed. All civilizations that once reached their heyday were immediately scorched to earth by the actions of the Mongolian troops. This was the beginning of the destruction of Islamic literacy because all evidence of books was destroyed and the deaths of experts in the field of knowledge who were sources of studying knowledge.